2006
DOI: 10.1002/gps.1501
|View full text |Cite
|
Sign up to set email alerts
|

Family conflict in dementia: prodigal sons and black sheep

Abstract: Dementia may be a great family divider, particularly when there are cracks in family solidarity. The understanding of family conflict in dementia has ramifications for both clinical and medico-legal practice. These findings may encourage family-centered interventions which address family dynamics and interpersonal conflict. They may also assist in capacity assessments of persons with dementia who change legal documents because of family conflict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 29 publications
0
41
0
6
Order By: Relevance
“…Behavioural changes rather than the level of disability appear to be correlated with caregiver distress and burden in FTD [7] , although very few studies have been conducted. It is almost certain that other factors such as individual characteristics of caregivers including gender [10] , personal resources, family psychodynamics [11] , coping strategies and caregiver health are likely to play an important role in the genesis of stress, since these factors emerge repeatedly in studies of families coping with other dementias [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural changes rather than the level of disability appear to be correlated with caregiver distress and burden in FTD [7] , although very few studies have been conducted. It is almost certain that other factors such as individual characteristics of caregivers including gender [10] , personal resources, family psychodynamics [11] , coping strategies and caregiver health are likely to play an important role in the genesis of stress, since these factors emerge repeatedly in studies of families coping with other dementias [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, dementia patients often lack the recognition of their own illness at an early stage of the disease, which makes it more difficult for care providers to approach them [31,32,33,34]. Moreover, in spite of the expectation that the family is a basic resource to support the dementia patient, dementia can cause conflicts among family members and sometimes even lead to abuse [35,36,37]. To solve these problems, our analysis suggested that increasing awareness of the illness among citizens is particularly important, including warning people that anyone is susceptible to dementia, as was shown previously [38].…”
Section: Discussionmentioning
confidence: 99%
“…Older people with mental illness, particularly dementia, are vulnerable to influence by others by virtue of impaired judgement and inability to appraise others (Peisah et al, 2006). Sometimes they are persuaded to marry inappropriately by others who seek to gain by such unions, constituting a type of abuse that has hitherto received little attention in the literature.…”
Section: Introductionmentioning
confidence: 97%